Cervical Leiomyoma in Pre-Menopausal Woman: A Case Report - Nadila Arisa Andriani; Saphira Ayu Suwantari; Hanif Reza (Faculty of Medicine, Universitas Diponegoro, 2022)
ABSTRACT Background: The most common pelvic tumors in women of reproductive age are uterine fibroids or known as leiomyomas, the frequency of cervical leiomyomas is about 1 to 2%. Leiomyoma which causes symptoms requires surgery, the most frequent surgical procedure is hysterectomy. Nevertheless, the management of cervical leiomyomas in premenopausal women remains a challenge in order to preserve the uterus whereas future pregnancy is still possible. Therefore, hysterectomy is not the preferred procedure. We present a case of a 47-year-old, multiparous woman with cervical leiomyoma that was treated with myomectomy and curettage to give an overview of how to treat cervical leiomyoma in patients who wanted to preserve their fertility.Case Presentation: A 47-year-old woman, P3A0, presented to the emergency department at Sultan Agung Islamic Hospital with a mass spontaneously protruding from the vagina a few hours before admission with a mass spontaneously protruding from the vagina, lower abdominal and heavy vaginal bleeding. The gynecological examination revealed a mass with a reddish surface and blood protruding out of the introitus. The dimensions of the mass were 20 cm x 8 cm x 12 cm. The mass is mobile, painful, tender on palpation, and seemed to be originating from the cervix. Myomectomy and curettage were performed. The histopathology result was suggestive of benign leiomyoma.Conclusion: In conclusion, this was a case of a patient with symptoms associated with cervical leiomyoma who was effectively treated with myomectomy and curettage. Myomectomy is considered the most frequent therapy for symptomatic myomas for women who desire to preserve their fertility.